팀 기반 전투형 게임에서 여성 게이머가 선호하는 여성 캐릭터에 대한 실증적 조사 연구 - 송두헌(Doo Heon Song) (한국정보통신학회논문지, 2021)
While there is no apparent gender difference on the number of game players and playing time in market survey especially if the age group is under 30, there still exists a strong gender stereotype on female characters with sexual objectification especially in team based battle games. Furthermore, there seldom exists any research on female gamers in this genre. In this paper, we investigate the preference of female characters and reasons of their choice among female gamers with Overwatch and Cypers which are recognized as having enough female players. In Overwatch with 231 responses, subjects prefer 'girl-crush' characters such as non-sexual Ana who age is in 60s. However, in Cypers that does not have female warrior character, subjects' preference is more affected by appearance but those characters with less functional ability are not frequently used in playing. Such practical avatar choice is often discovered among male players thus there is no gender difference in this case. 최근 조사에서 30세 미만 게임 사용자들 간에는 그 수와 플레이 시간 등에서 성차가 거의 없다. 그러나 전투형 게임은 캐릭터의 설정 등에서 성 고정관념이 팽배하며 특히 여성 캐릭터의 성 도구화 문제가 대두되기도 했고 여성 게이머 관련 연구도 거의 없다. 본 논문은 여성 참여도가 높은 팀 기반 전투형 게임인 오버워치와 사이퍼즈의 여성 캐릭터에 대한 여성 게이머들의 선호도와 그 이유를 조사해 보았다. 총 231명이 응답한 오버워치 설문 조사에서는 성적 매력과는 거리가 있는 60대의 아나가 2위로, 걸 크러쉬형 캐릭터를 선호하는 캐릭터 인지 패턴이 나타났다. 반면 전사형 캐릭터가 없는 사이퍼즈의 경우에는 선호한 여성 캐릭터들은 외형적 매력이 영향을 미쳤는데 그 캐릭터들은 실제 플레이에는 제대로 사용되지 않음을 발견하였다. 즉, 외형적 매력은 캐릭터의 선호도는 높지만 수행 능력이 따라오지 않는다면 실제 게임에서 활용하지 않는다는 실리적 선택이 보이는데 이는 남성 게이머들과 차이가 없다.